Pengaruh persepsi pasien tentang marketing mix terhadap pemanfaatan pelayanan rawat inap - Firdaus , Fernanda Putra; Murdiyanto, Edi; Munawaroh, Nuril Aulia (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Inpatient services are one of the important indicators in measuring the quality and performance of hospitals. Hospitals need to pay attention to marketing strategies, especially marketing mixes to attract and retain patients. Patient perceptions of marketing mix elements such as product, price, place, promotion, people, process, and physical evidence greatly influence patient decisions in utilizing inpatient services. Purpose: To determine the effect of patient perceptions of the marketing mix on the utilization of inpatient services. Method: Quantitative research with a cross-sectional approach. The research sample used was 122 inpatients at Kediri Baptist Hospital. The sampling technique was probability sampling with a simple random sampling method. Results: The product moment correlation test conducted on patient perceptions of the marketing mix on the utilization of inpatient services, obtained a sig value of 0.000. The sig value is smaller than 0.05 (0.000> 0.05) which indicates that there is a significant influence between patient perceptions of the marketing mix on the utilization of inpatient services with a value of r = 0.752 which means it is classified as strong. Meanwhile, the magnitude of the contribution of the determinant coefficient and the determinant coefficient is KP = r².100% = 0.752² which means that the influence of patient perceptions of the marketing mix on the utilization of inpatient services is 56% and the remaining 44% is determined by other variables. Conclusion: There is a significant influence between patient perceptions of the marketing mix on the utilization of inpatient services. Suggestion: The hospital can conduct a customer satisfaction survey according to the specified period to increase the number of patient visits. Keywords: Inpatient; Marketing Mix; Patient Perception; Service. Pendahuluan: Pelayanan rawat inap merupakan salah satu indikator penting dalam mengukur mutu dan kinerja rumah sakit. Rumah sakit perlu memperhatikan strategi pemasaran, khususnya bauran pemasaran (marketing mix) untuk menarik dan mempertahankan pasien. Persepsi pasien terhadap elemen marketing mix, seperti produk, harga, tempat, promosi, orang, proses, dan bukti fisik sangat memengaruhi keputusan pasien dalam memanfaatkan layanan rawat inap. Tujuan: Untuk mengetahui pengaruh persepsi pasien tentang marketing mix terhadap pemanfaatan pelayanan rawat inap. Metode: Penelitian kuantitatif dengan pendekatan cross sectional. Sampel penelitian yang digunakan sebanyak 122 pasien rawat inap RS Baptis Kediri. Teknik pengambilan sampel secara probability sampling dengan metode simple random sampling. Hasil: Uji korelasi product moment yang dilakukan terhadap persepsi pasien tentang marketing mix terhadap pemanfaatan pelayanan rawat inap, ditemukan nilai sig 0.000. Nilai sig lebih kecil dari 0.05 (0.000>0.05), menunjukkan bahwa ada pengaruh yang signifikan antara persepsi pasien tentang marketing mix terhadap pemanfaatan pelayanan rawat inap dengan nilai r= 0.752 yang berarti tergolong kuat. Sementara itu, besarnya sumbangan koefisien determinan dan koefisien penentu sebesar KP=r².100%=0.752², artinya pengaruh persepsi pasien tentang marketing mix terhadap pemanfaatan pelayanan rawat inap sebesar 56% dan sisanya 44% ditentukan oleh variabel lain. Simpulan: Terdapat pengaruh yang signifikan antara persepsi pasien tentang marketing mix terhadap pemanfaatan pelayanan rawat inap. Saran: Pihak rumah sakit dapat melakukan survei kepuasan pelanggan sesuai periode yang ditentukan agar meningkatkan jumlah kunjungan pasien. Kata Kunci: Marketing Mix; Pelayanan; Persepsi Pasien; Rawat Inap.